DEMOGRAPHIC CHARACTERISTICS, PRESENTATIONS AND TREATMENT OUTCOME OF PATIENTS WITH PROLACTINOMA - Malik, Sarwar; Hussain, Syed Zubair; Basit, Rabia; Idress, Najia; Habib, Aysha; Zaman, Muhammad; Islam, Najmul (Journal of Ayub Medical College Abbottabad, 2014)
Background: Prolactinomas are the most common type of functional pituitary tumours. The objective of this study was to determine demographic profile of patients with prolactinomas, and to compare the outcomes in patients treated with Cabergoline versus those receiving Bromocriptine treatment. Methods: This descriptive study was conducted at Endocrinology Section, Department of Medicine, Aga Khan University Hospital, Karachi, Pakistan. We reviewed the medical record of 68 patients with prolactinoma. Data about demographic characteristics, clinical presentation and treatment were entered on a pre-designed pro forma. Results: Out of the total 68 patients, 36.8% were males and 63.2% were females, with a mean age of 34±10.7 years. The most frequent presenting complaint amongst the patients was of headache, present in 57.4% patients. Galactorrhea, amenorrhea and infertility were next highest reported symptoms. Results of the tumour size on initial MRI showed macroprolactinomas 52.9% (36), microprolactinomas in 33.8% (23), and giant prolactinomas in 13.3 % (9) patients. Decreasing trend of prolactin levels were also seen on follow up visits at 9 months and 12 months. Tumour size was decreased in 48.53% (33) patients and lesion completely disappeared in 16.18% (11) patients after 6 months of treatment and also almost similar trend in tumour size change was seen after one year. There was no significant difference between the two drugs in bringing prolactin to normal range at each follow up duration. Conclusion: Most of the prolactinoma patients were females and the common the most frequent presenting complaint was headache. The decreasing trend of serum prolactin and tumour size reduction in patients was noted, suggesting the beneficial impact of medical therapy as it is the first line treatment modality in these patients. Keywords: Prolactinoma, Prolactin, Tumour size, Bromocriptine, Cabergoline